The Value of Vocational Education High School Type and Labor Market Outcomes in Indonesia - Newhouse, David (The World Bank, 2009)
This paper examines the relationship between the type of senior high school attended by Indonesian youth and their subsequent labor market outcomes. This topic is very timely, given the government's recent decision to dramatically expand vocational enrollment. The analysis controls for an unusually rich set of predetermined characteristics, and exploits longitudinal data spanning 14 years to separately identify cohort and age effects. There are four main findings. First, students are sorted into different school types largely on the basis of their entering exam score. Public schools attract the highest-scoring students, while private vocational schools serve the lowest-scoring students. Second, after controlling for a variety of characteristics, including test scores, male public school graduates earn a substantial premium over their privately schooled counterparts. Third, private vocational school graduates fare at least as well as private general graduates, despite coming from more disadvantaged socioeconomic backgrounds. Finally, the returns to public vocational education have declined sharply for the most recent cohort of men. This raises important concerns about the current expansion of public vocational education, and the relevance of the male vocational curriculum in an increasingly service-oriented economy